Intergenerational transmission of religious beliefs and practices and the reduction of adolescent delinquency in urban Thailand - Chamratrithirong A. (2014)
This study examines the intergenerational transmission of family religion as measured by parent's and adolescent's beliefs and practices in Buddhism, and its relation to delinquent behaviors among early adolescents in Thailand. The data set is from the Thai Family Matters Project 2007, a representative sample of 420 pairs of parents and teens in Bangkok. A structural equation model is employed for the analysis. The intergenerational transmission and the direct and indirect association between parents' and adolescents' beliefs and practices in Buddhism and adolescents' minor and serious delinquent behaviors are revealed to be significant, controlling for secular parental monitoring. Spirituality within the family can play an important role in preventing delinquency among early adolescents. Policies in the areas related to family empowerment and delinquency prevention may need to consider integrating both secular and non-secular program inputs in their implementation design. © 2012 The Foundation for Professionals in Services for Adolescents.